Influence of weather conditions and fertilizer systems on the winter wheat yield - Barabolia, O.; Doronin, S. (Scientific Progress & Innovations, 2023)
Growing different varieties of winter wheat, combining high productivity with adaptability, is impossible without studying the patterns of variability of yield formation depending on weather and soil conditions of the territory, fertilizer systems and fertilizer options. The aim of the study is to determine the effect of weather conditions on the formation of winter wheat yields of varieties Vidrada, Sahaidak and Orzhytsia using different fertilizer systems. The study was conducted during 2020-2022 in the production conditions of the forest-steppe zone of Ukraine. Winter wheat varieties of Ukrainian selection were studied. They are characterized by high productivity, sufficient resistance to diseases and stress factors. It was determined that the most favorable by temperature and precipitation during the growing season was 2021, hence the yield of all experimental varieties has increased in comparison with 2020. The year 2022 was the least favourable due to a prolonged cool spring, a dry June and heavy rainfall in July. The crop capacity of winter wheat under these conditions fluctuated against the background without basic fertilization with different variants of additional fertilization and fertilization by varieties in 2021 and 2022 respectively: Vidrada – 6.9–7.6 t/ha and 5.2–5.6 t/ha; Sahaidak – 8.0–8.6 t/ha and 7.2–7.6 t/ha; Orzhytsia – 6.0–6.4 t/ha and 5.1–5.6 t/ha. It was determined that the influence of weather conditions on the yield of winter wheat of the experimental varieties is on average 10–12 %. The application of N30P60K60 with the main fertilizer contributed to increasing the average yield of the experimental varieties of wheat by 9.1–13.2 % under different variants of fertilization and was the most effective for the additional fertilizer N 60 with the additional fertilizer Mono Copper and CAM. The most effective over the years of research additional fertilizer N 60 with fertilizer variants Mono Copper, CAM or their combined use in the phase of tillering on the background without basic fertilizer (the average yield of varieties): Vidrada – 6.3–6.7 t/ha; Sahaidak – 6.3–6.7 t/ha; Orzhytsia – 5.9–6.3 t/ha. On a background of application of N30P60K60 with the additional fertilizer N 60 the highest average yield for 2020–2022 is provided by feeding with CAM or its compatible use with Mono Copper for the following varieties: Vidrada – 7.1–7.5 t/ha; Sahaidak – 9.1–9.5 t/ha; Orzhytsia – 6.7–7.1 t/ha.